Structured teaching programme on knowledge about polycystic ovarian syndrome among adolescent girls - Rawat, Sonia; B., Gomathi; Kumar, Laxmi; V., Mahalingam (International Journal of Research in Medical Sciences, 2017)
Background: Polycystic ovarian syndrome is a common female endocrine disorder affecting 4 – 18% of women in their reproductive age. It is common in adolescent girls. Polycystic Ovarian Syndrome affects throughout the life and produce gynaecological and metabolic health problems. The aim of this study to create the awareness about the polycystic ovarian syndrome to the adolescent girls. Methods: A Quantitative approach with pre- experimental design was used to study the effectiveness of STP on Poly Cystic Ovarian Syndrome. Ninety-four adolescent girls aged between 15 – 18 years were conveniently selected. Data was collected by using Structured Knowledge questionnaire. Results: The mean post-test knowledge score (22.55± 3.57) was higher than that of mean pre-test mean knowledge score (11.13± 3.32) and the mean difference was11.42. The ‘t’ calculated value was 23.45 which is higher than the tabulated value of 1.98 (df 93 at p< 0.05). Therefore, research hypothesis was accepted. So, it can be interpreting that structured teaching programme is effective in improving the knowledge of adolescent girls. Conclusions: The findings of the study revealed that STP was effective in enhancing the knowledge of adolescent girls on PCOS. Hence the study concluded that structured teaching programme had a great potentiality to increase the awareness on PCOS.